Asymmetric total synthesis of yuzurimine-type Daphniphyllum alkaloid (+)-caldaphnidine J - Lian-Dong Guo (Nature Portfolio, 2020)
Despite being known for more than 50 years, yuzurimine-type alkaloids have not been accessed by total synthesis. Here, the authors report the first enantioselective total synthesis of (+)-Caldaphnidine J, a highly complex yuzurimine-type Daphniphyllum alkaloid.